(untitled) (Journal of Naval Architecture and Marine Engineering, 2013)
A numerical study is conducted to analyze the effect of Joule heating and MHD (magnetohydrodynamic) free convection flow and heat transfer along a uniformly heated vertical wavy surface with temperature dependent variable viscosity and thermal conductivity. The governing boundary layer equations with associated boundary conditions for phenomenon are converted to non-dimensional form using the appropriate transformations. The resulting nonlinear system of partial differential equations are mapped into the domain of a vertical flat plate and solved numerically by employing implicit finite difference method, known as the Keller-box scheme. The behavior of the fluid in the ranges of Joule heating parameter (0.02.0), viscosity parameter (0.020.0) and thermal conductivity parameter (0.0 10.0) are explained in details. It is found that the flow and temperature fields are strongly dependent on the above stated parameters for the ranges considered. The skin friction coefficient and the rate of heat transfer are also presented. The skin friction coefficient and the heat transfer for different values of Prandtl number Pr are compared with previously published work and are found to be in excellent agreement. DOI: http://dx.doi.org/10.3329/jname.v10i2.11707